DAMPAK EKOWISATA BAHARI DALAM PERSPEKTIF KESEJAHTERAAN MASYARAKAT DAN KELESTARIAN LINGKUNGAN PESISIR - Komang Jaka Ferdian; Iqbal Aidar Idrus DM; Simson Tondo (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
The tourism sector is an important part of realizing the economic equality of the community, especially those in the Coastal areas that are highly dependent on marine resources directly. Tourism industrialization provides space for investors or capital owners to enter, thus leading to a view of capitalism that raises grabbing resources. Privatization and industrialization of tourism not only have an impact on people's lives but also affect the quality of the environment around tourism sites. Industrial tourism is only felt by a handful of people so that the need for tourism management is environmentally friendly and the welfare of the surrounding community. This article uses descriptive qualitative methods and uses literature studies from various sources. Explanation of the contents of this article finds that tourism industrialization has an impact on community conflict, socio-cultural changes and the formation of power relations. Indonesia can be a pilot from other countries in developing ecotourism. Indonesia is currently an area that has natural beauty that can be used as an ecotourism potential. For example, regions in Indonesia that should be used as ecotourism objects include Minahasa, West Sumatra and Lombok.Keywords: Ecotourism, Tourism Industry, Marine Ecotourism.